Photothermal tumor ablation in mice with repeated therapy sessions using NIR-absorbing micellar hydrogels formed in situ. (July 2015) - Hsiao, Chun-Wen; Chuang, Er-Yuan; Chen, Hsin-Lung; Wan, Dehui; Korupalli, Chiranjeevi; Liao, Zi-Xian; Chiu, Ya-Ling; Chia, Wei-Tso; Lin, Kun-Ju; Sung, Hsing-Wen
Abstract: Repeated cancer treatments are common, owing to the aggressive and resistant nature of tumors. This work presents a chitosan (CS) derivative that contains self-doped polyaniline (PANI) side chains, capable of self-assembling to form micelles and then transforming into hydrogels driven by a local change in pH. Analysis results of small-angle X-ray scattering indicate that the sol–gel transition of this CS derivative may provide the mechanical integrity to maintain its spatial stability in the microenvironment of solid tumors. The micelles formed in the CS hydrogel function as nanoscaled heating sources upon exposure to near-infrared light, thereby enabling the selective killing of cancer cells in a light-treated area. Additionally, photothermal efficacy of the micellar hydrogel is evaluated using a tumor-bearing mouse model; hollow gold nanospheres (HGNs) are used for comparison. Given the ability of the micellar hydrogel to provide spatial stability within a solid tumor, which prevents its leakage from the injection site, the therapeutic efficacy of this hydrogel, as a photothermal therapeutic agent for repeated treatments, exceeds that of nanosized HGNs. Results of this study demonstrate that this in situ -formed micellar hydrogel is a highly promising modality for repeated cancer treatments, providing a clinically viable, minimally invasive phototherapeutic option for therapeutic treatment.